Dietary Lauric Acid Supplementation Positively Affects Growth Performance, Oxidative and Immune Status of European Seabass Juveniles - Filipa Fontinha; Nicole Martins; Rui Magalhães; Helena Peres; Aires Oliva-Teles (Fishes)
Lauric acid (LA), a medium-chain fatty acid (C12), can promote growth performance and decrease oxidative damage and lipid deposition in animals. This study aimed to evaluate the effect of dietary supplementation of lauric acid as a functional ingredient on European seabass juveniles’ growth performance and intestine antioxidant and immunological status. For this purpose, four practical diets were formulated to be isoproteic and isolipidic, including 0, 0.5, 1, and 2% of LA, and fed to triplicate groups of European seabass juveniles (~12.7 g) for 61 days. Dietary LA supplementation did not affect growth performance, feed utilization, or whole-body composition, but feed intake increased at a concentration-dependent level. However, the plasmatic triglyceride content was increased at the higher level of LA supplementation. In the intestine, catalase and glutathione reductase activities and lipid peroxidation levels were lower in fish fed the 1% LA diet than in the control group. The hepatic LPO level was higher in fish fed 0.5% LA than in the control group. Fish fed the 1% LA diet presented lower intestinal expressions of caspase 3, tumor necrosis factor-alpha, interleukins 10, 6, and 1-β, and a lower plasma white blood cell number. Overall, up to 2% dietary supplementation of lauric acid as a functional ingredient showed a trend to improve European sea bass juveniles’ growth performance without affecting feed utilization. Moreover, 1% dietary inclusion of LA reduced intestinal lipid peroxidation and downregulated pro-inflammatory and anti-inflammatory genes, thus enhancing the intestine’s homeostatic status.